Currency and Commodity Return Relationship Under Extreme Geopolitical Risks: Evidence From the Invasion of Ukraine - Dodd, Olga; Fernández-Pérez, Adrian; Sosvilla-Rivero, Simon (Taylor & Francis, 2022)
We examine the relationship between currency and commodity returns around the invasion of Ukraine in February 2022. We find that the expected positive contemporaneous relationship between currency and commodity returns reverses and becomes negative during this period of extreme geopolitical risks. In addition to commodity returns, currency returns around the invasion of Ukraine are significantly affected by geopolitical factors, particularly geographic distance to the war. Our results indicate that a war between two major commodity-exporting countries significantly affects global currency pricing.
Keywords: 38 Economics; 3502 Banking, Finance and Investment; 3801 Applied Economics; 35 Commerce, Management, Tourism and Services; 1117 Public Health and Health Services; 1402 Applied Economics; 1502 Banking, Finance and Investment; Economics; Finance; 3502 Banking, finance and investment; 3801 Applied economics; 3899 Other economics; Foreign exchange rates; currency return; commodity returns; Ukraine–Russia war; geographic distance